Hubungan Karakteristik Sosial Ekonomi dan Biaya Produksi terhadap Pendapatan Usahatani Lada di Daerah Perbatasan - Paulina, Yohana; Yurisinthae, Erlinda; Kurniati, Dewi (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2024)
Pepper farmers' income is often influenced by various factors, both socio-economic and production costs. The aim of this research is to analyze the correlation between farmers' socio-economic characteristics and production costs on pepper (Piper nigrum L) with farming income. The data analysis method used is Spearman Rank Correlation and descriptive data scaling techniques. The research findings show that, regarding farmers' socio-economic characteristics, the factor that has a strong relationship with pepper farming income is age, while education and experience have a moderate relationship. Land area and dependents, on the other hand, show a weak relationship. In terms of production costs, the factor that has a strong relationship is fertilizer expenses, the factor with a moderate relationship is chemicals, while labor, depreciation, and taxes do not show a significant relationship.